Peran Media Sosial Dalam Meningkatkan Destinasi Afektif Untuk Mempengaruhi Niat Berkunjung Pada Objek Wisata di Kota Solo - Didik Setyawan (Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of social media in shaping affective destinations and its implications for visiting intentions at tourist attractions in Solo City. Covid-19 has resulted in a decline in visits and an increase in the use of social media as a means of tourism promotion. Visual content and narratives about tourist destinations uploaded on social media are believed to shape tourists' perceptions, emotional assessments, and intentions to visit Solo City. This research uses a quantitative approach with a causal design and survey method. Data was collected through an online questionnaire distributed to 200 respondents from the general public in Indonesia who use Instagram social media and follow the @jelajah_solo account. The sampling technique used non-probability sampling with the purposive sampling method. Data analysis was carried out using Structural Equation Modeling (SEM) using AMOS to test the measurement model and structural model. The results of the study showed that all the hypotheses proposed were supported. These findings indicate that social media management that is able to present an attractive destination image, elements of novelty, and good quality information will increase tourists' affective destinations which ultimately encourages the intention to visit tourist attractions in Solo City.